Transnational Biographies Changing We-images, Collective Belongings and Power Chances of Migrants and Refugees - Rosenthal, Gabriele (Universitätsverlag Göttingen, 2022)
Every day many people leave the place where they live and move to some other place, where they settle permanently or stay for many years. The contributions to this volume are based on the results of three empirical research projects which set out to investigate the situation of migrants in Jordan, Brazil, Germany and other European countries. The articles focus on migrants at their place of arrival and ask questions such as: How do they look back on their life histories and migration paths? What dynamics and processes led up to their migration projects and how do they explain their motives? The studies in this volume show that leaving and arriving are interrelated: leaving one's home region is part of a long process, partly planned and partly unplanned, which is determined by complex collective, familial and individual constellations, and which has significant consequences for the action patterns and participation strategies of migrants in their arrival societies. This book also shows which constellations enable some migrants to realize their goals in their present situation, and which constraints or obstacles make it impossible for others to do so.